Physical, mechanical and thermal properties of wood/zeolite/plastic hybrid composites - Kaymakci, Alperen; Gulec, Turker; Hosseinihashemi, Seyyed Khalil; Ayrilmis, Nadir (Universidad del Bio Bio, 2017)
Effect of zeolite content on the physical, mechanical and thermal properties of wood plastic composites was investigated in this study. To meet this objective, pine wood flour (0, 10, 20, 30, 40, 50 wt%) with compatibilizing agent, zeolite (0, 10, 20, 30, 40, 50 wt%), and polypropylene were compounded in a twin screw co-rotating extruder. The mass ratio of the wood flour to polypropylene was 50/50 (w/w) in all compounds. Test specimens were produced using injection molding machine from the pellets. Physical and mechanical, and thermal (Thermogravimetry Analysis/Differential Scanning Calorimetry) properties of the wood plastic composites were determined. The water absorption and thickness swelling properties of wood plastic composites improved with increasing zeolite content. The flexural and tensile properties of the wood plastic composites decreased with increasing zeolite content. All the wood plastic composites provided the values of flexural strength (58,4-72,9 MPa) and flexural modulus (2718-5024 MPa) that were well over the requirement by the standard specified in ASTM D 6662. The mass loss rates values of wood plastic composites increased with increasing zeolite contents. The Differential Scanning Calorimetry analysis showed that the melt crystallization enthalpies and degree of crystallization of wood plastic composites decreased with increasing zeolite content. The decrease in the Tc and Xc indicated that zeolite was the poor nucleating agent for the wood plastic composites.
Keywords: thermoplastic composites; Manufactures; Pinus sylvestris; Forestry; SD1-669.5; thermal stability.; thermal stability; TS1-2301; swelling; technological properties